2015
DOI: 10.1108/jeee-03-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Studying the influence of entrepreneurial attributes, subjective norms and perceived desirability on entrepreneurial intentions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 38 publications
8
34
0
15
Order By: Relevance
“…Further the findings of studies of [35]; [22]; [29] have obtained similar results. According to the findings of the study a statistically significant relationship is exist between PBC and EI.…”
Section: Indirect Effect Of Rmsupporting
confidence: 77%
See 1 more Smart Citation
“…Further the findings of studies of [35]; [22]; [29] have obtained similar results. According to the findings of the study a statistically significant relationship is exist between PBC and EI.…”
Section: Indirect Effect Of Rmsupporting
confidence: 77%
“…A study done by [28] with a sample of 95 secondary school students conclude that ATE play a role in actively promoting and determining EI. [29] also conducted a study 220 students and found that ATE significantly and positively related with EI. Further, similar studies were carried out by [30]; [31,19,20,32] are also supported and in line with the results of this study.…”
Section: Indirect Effect Of Rmmentioning
confidence: 99%
“…Therefore, their decision to take action is related to the important person's opinion (Fethi & Mohammed, 2019). Indeed, Yousaf et al (2015) remarked that subjective norms have an important role in developing students' intentions to become entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian terdahulu yang telah dilakukan oleh Astuti dan Martdianty (2012), menyatakan bahwa subjective norm memiliki pengaruh yang signifikan terhadap entrepreneurial intention. Hasil serupa ditemukan pula pada penelitian yang dilakukan oleh Yousaf, Shamim, Siddiqui, dan Raina (2014). Subjective norm merupakan suatu keyakinan yang ada dalam diri seorang individu akan dukungan dari lingkungan sekitarnya.…”
Section: Pembahasanunclassified